Avaliação dos impactos de cenários de mudanças no uso do solo na hidrologia da bacia hidrográfica do rio Xingu - Cunha, Zandra Almeida da (2021)
The Xingu River watershed (XRW) has great importance in the economic development of Brazil, given the intensification of agricultural activities in the region. These activities result in increasing deforestation rates in the basin. In this sense, the use of hydrological models to assess impacts on hydrological behavior due to changes in land use becomes a viable tool for the management of water resources. This study aimed to evaluate the potential of the Lavras Simulation of Hydrology (LASH) model to represent the main hydrological processes and hydrological indicators at XRW and, also, to simulate the possible hydrological impacts in face of different scenarios of land-use changes in the hydrological behavior of the basin. The evaluated scenarios addressed the increase of 50% (C1) and 100% (C2) of the forest areas to pasture areas. Scenarios C3 and C4 comprise an increase of 50% and 100% of forest areas to soybean cultivation areas. Finally, C5 addressed the increase of 100% of pasture areas to soybean cultivation areas. The results obtained in the calibration and validation of the LASH model allowed to verify that the performance in XRW was superior to the other studies already carried out with the model. Furthermore, it was possible to infer that the performance of the LASH model was superior to that of other models used in hydrographic basins of the Amazon Forest and the Cerrado. Analyzing the estimated hydrograms compared to those observed, it was possible to observe that the model performed well in the representation of the average daily and monthly flows of XRW. Likewise, the LASH model underestimated XRW's minimum and maximum flow values. As for the components of the water balance, the results indicated good performance of the model for the estimate in XRW. Furthermore, the components of greater participation in the outputs of the water balance at XRW were real evapotranspiration (ETr) and current storage (At). The results of the “Proxy Basin Test” validation, on the other hand, made it possible to infer that the parameters of the LASH model calibrated in the XRW outlet were representative for the Iriri River watershed. Analyzing the hydrographs of each scenario, it was observed that, in general, the changes in the uses of the soil at XRW led to an increase in flow production, mainly at peak flows. In the most critical scenarios, the increase in runoff was 16.1% in C2 and 18.6% in C4. The estimate of the components of the water balance indicated that, in general, the deforestation scenarios in XRW resulted in reductions in the rates of ETr, interception, and At, in up to 4.9%, 11.7%, and 21.9%, respectively. It was possible to conclude that the current deforestation rates have the potential to significantly change the magnitude of the components of the hydrological cycle in the Amazon.